PERAN END CHILD PROSTITUTION, CHILD PHORNOGRAPHY, AND TRAFFICKING OF CHILDREN FOR SEXSUAL PURPOSES (ECPAT) DALAM MENGATASI MASALAH EKSPLOITASI SEKSUAL KOMERSIAL ANAK (ESKA) DI FILIPINA (2009-2013) - Sitanggang, Yenni Heflin; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to find out the role of End Child Prostitution, Child Phornography, and Trafficking of Children For Sexual Purposes (ECPAT) against child exploitation for sexual purposes (CSEC) in Phillipiness in 2009-2013. ECPAT is one of non governmental organization focus to end CSEC. CSEC is a form of human trafficking where children are treated as a commercial object by using coercion and violence that lead to form of child labor. CSEC become a great threat in many countries ecpecially in countries with social and economic problems. This research used NGO theory and Role Theory and pluralism perperctive to see the role of ECPAT against CSEC. The results shows ECPAT efforts to against CSEC through campaign, partnership with government, cooperation, other NGOs, etc. Philiphiness government and ECPAT oversee the implementation of child laws in the Philippines. ECPAT also formed a partnership with The Body Shop and cooperating with privat sectors such as travels agencies, hotel, airport, internet service provider. These effort need support from all of bases ini Philiphiness.Keywords : CSEC, ECPAT, International Campaign, NGO, Child Youth Participation.